Preparation method of high interface strain polymer electrolyte for lithium metal battery
通过在聚合物电解质中调整氟元素与氧元素的占比,提升界面体积形变,解决了锂金属电池中锂离子不均匀沉积及锂枝晶生长的问题,实现了更好的循环稳定性。
Patent Information
- Application Number
- CN202411819707.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
There are problems of uneven deposition of lithium ions and growth of lithium dendrites at the electrolyte/electrode interface of polymer quasi-solid lithium metal batteries, which affect battery performance.
By designing the proportion of fluorine and oxygen elements in the polymer electrolyte segment, the interface volume deformation during polymer deliquification ions can be increased, the potential difference between the electrolyte/lithium metal interface can be reduced, and the interface uniform lithium deposition can be achieved.
Effectively inhibit the growth of lithium dendrites, uniformize the interfacial lithium deposition, and improve the circulation stability of lithium metal batteries.
Smart Images

Figure CN119638916A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium metal batteries, and in particular relates to a method for preparing a high interface strain polymer electrolyte for lithium metal batteries. Background Art
[0002] The development of polymer-based quasi-solid-state lithium metal batteries is of great significance. Due to their low manufacturing cost, flexible structural design and good performance, polymer-based quasi-solid-state lithium metal batteries have broad application prospects in electric transportation, energy storage, consumer electronics and wearable devices. Through further technological progress and process optimization, polymer-based quasi-solid-state lithium metal batteries are expected to become one of the core directions of future battery technology.
[0003] Although polymer quasi-solid-state lithium metal batteries have unique advantages in improving energy density and safety, they face problems such as uneven deposition of lithium ions at the electrolyte / electrode interface and lithium dendrite growth. The initial driving force for lithium dendrite growth is the high potential difference at the electrolyte / lithium metal interface, which will accelerate the uneven deposition of ions and further lead to dendrite growth. When lithium ions escape from the electrolyte interface, the degree of polymer deformation can be called the lithium ion partial molar volume of the electrolyte. High lithium ion partial molar volume corresponds to a higher polymer interface deformation, and high interface deformation can effectively reduce the potential difference at the electrolyte / lithium metal interface, thereby homogenizing interfacial lithium deposition and inhibiting dendrite growth (Advanced Energy Materials, 2023, 13 (47): 2302643; Journal of The Electrochemical Society, 2004, 151 (6): A880; Nature materials, 2020, 19 (7): 758-766).
[0004] Therefore, designing a polymer electrolyte with high interface deformation will help solve problems such as uneven lithium ion deposition and lithium dendrite growth at the electrolyte / electrode interface, and further improve the performance of polymer quasi-solid-state lithium metal batteries. Summary of the invention
[0005] In response to the problems of uneven lithium ion deposition and lithium dendrite growth at the electrolyte / electrode interface in existing polymer quasi-solid-state lithium metal batteries, the present invention provides a method for preparing a high interfacial strain polymer electrolyte for lithium metal batteries. By designing the ratio of fluorine to oxygen in the polymer electrolyte chain segments, the interfacial volume deformation of the polymer during lithium ion desorption is increased, thereby reducing the potential difference at the electrolyte / lithium metal interface, thereby achieving uniform lithium deposition on the interface.
[0006] In order to achieve the above purpose, the technical method adopted by the present invention is as follows:
[0007] A method for preparing a high interfacial strain polymer electrolyte for a lithium metal battery comprises the following steps:
[0008] Step 1, adding lithium salt into an organic solvent and stirring to obtain a precursor solution A with a concentration of 0.5 to 3M;
[0009] Step 2, mixing a polymer monomer, an initiator, a cross-linking agent and a lithium salt, and stirring to obtain a precursor solution B; wherein the molar ratio of the polymer monomer, the initiator and the cross-linking agent is (98-100): (0.5-2): (1-3); the concentration of the lithium salt in the precursor solution B is 0.5-3M; the polymer monomer is at least one of 2,2,3,4,4,4-hexafluorobutyl acrylate, 1H,1H,2H,2H-nonafluorohexyl acrylate, 2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptyl acrylate, and 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate;
[0010] Step 3, mixing precursor solution A and precursor solution B in a volume ratio of (0.5-2):(1-3), and stirring to form a composite solution C;
[0011] Step 4: Using the composite solution C as the electrolyte, assembling a lithium metal battery, and after drying, obtaining a high interfacial strain polymer electrolyte formed in situ at the interface between the positive and negative electrodes of the lithium metal battery.
[0012] Furthermore, the polymer monomers also include benzyl acrylate and / or butyl acrylate.
[0013] Furthermore, by adjusting the specific components and proportions of the polymer monomers in the precursor solution B, the ratio of fluorine elements to oxygen elements contained in the resulting high interfacial strain polymer electrolyte chain segment is controlled to be (5-15):(1-3), thereby achieving high interfacial volume deformation.
[0014] Furthermore, the organic solvent is at least one of fluoroethylene carbonate, ethylene glycol dimethyl ether, 1,3-dioxolane, diethyl carbonate, and dimethyl carbonate.
[0015] Furthermore, the initiator is at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dimethyl azobisisobutyrate, and azobisisobutyramidine hydrochloride.
[0016] Furthermore, the cross-linking agent is polyethylene glycol diacrylate and / or ethylene glycol dimethacrylate.
[0017] Furthermore, the lithium salt is at least one of lithium hexafluorophosphate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium difluorooxalatoborate.
[0018] Furthermore, in step 4, the drying temperature is 60-80° C. and the drying time is 12-24 hours.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention proposes a method for preparing a high interfacial strain polymer electrolyte for lithium metal batteries. By designing the ratio of fluorine to oxygen in the polymer electrolyte chain segment, the coordination strength of Li-O in the polymer electrolyte bulk phase is reduced, and the interfacial volume deformation of the polymer during lithium ion removal is increased, thereby reducing the potential difference at the electrolyte / lithium metal interface, homogenizing interfacial lithium deposition, inhibiting lithium dendrite growth, and ultimately improving the cycle stability of the lithium metal battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 The deformation diagram of the electrolyte de-Li+ interface with time of the high interfacial strain polymer electrolyte obtained in Example 1 and the low interfacial strain polymer electrolyte obtained in Comparative Example 1;
[0023] Figure 2 The cycle diagram of Li||NCM811 battery assembled with the high interfacial strain polymer electrolyte obtained in Example 1 and the low interfacial strain polymer electrolyte obtained in Comparative Example 1;
[0024] Figure 3 This is a cycle diagram of a Li||Li symmetric battery assembled with the high interfacial strain polymer electrolyte obtained in Example 1 and the low interfacial strain polymer electrolyte obtained in Comparative Example 1. DETAILED DESCRIPTION
[0025] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with the examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. All raw materials of the present invention are not particularly limited in their sources, and can be purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0026] Example 1
[0027] This embodiment prepares a high interfacial strain polymer electrolyte for lithium metal batteries, which specifically includes the following steps:
[0028] Step 1, adding lithium bis(trifluoromethanesulfonyl)imide into fluoroethylene carbonate, stirring to obtain a precursor solution A with a concentration of 1 M;
[0029] Step 2: Mix 2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptyl acrylate, azobisisobutyronitrile, polyethylene glycol diacrylate and lithium bistrifluoromethanesulfonyl imide, and stir to obtain a precursor solution B; wherein the molar ratio of the polymer monomer, the initiator and the crosslinking agent is 100:0.5:1; and the concentration of the lithium salt in the precursor solution B is 2M;
[0030] Step 3, mixing precursor solution A and precursor solution B in a volume ratio of 1:1, and stirring to form a composite solution C;
[0031] Step 4. Using composite solution C as electrolyte, assemble a lithium metal battery, and after drying at 60° C. for 12 hours, obtain a high interfacial strain polymer electrolyte formed in situ at the positive and negative electrode interfaces of the lithium metal battery; wherein, according to the ratio of fluorine element to oxygen element in the chemical structure formula of the adopted polymer monomer 2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptyl acrylate, the ratio of fluorine element to oxygen element contained in the high interfacial strain polymer electrolyte segment can be determined, and the calculated ratio is 6:1.
[0032] In order to better illustrate the positive effect of the high interfacial strain polymer electrolyte obtained in this embodiment on lithium metal batteries, a transparent battery, a Li||NCM811 battery and a Li||Li symmetric battery are assembled for illustration.
[0033] When assembling a transparent battery, a clean copper foil is used as a counter electrode, a precursor solution A with a lithium salt concentration of 2M is used as an ion conductor, and a copper foil strip is used as a current collector and a conductor to assemble the transparent battery; the composite solution C obtained in this embodiment is dripped onto the copper foil using a pipette gun, and is placed in an oven at 60° C. for in-situ curing to obtain a coated copper foil; the transparent battery is placed under an optical microscope, and the coated copper foil and the clean copper foil are used as counter electrodes, respectively, and are connected to the positive and negative electrodes of a blue battery test workstation; a forced charging test is performed on the transparent battery, and the structural changes of the electrolyte surface of the coated copper foil when lithium ions are released are observed using an optical microscope, and the results are as follows: Figure 1 shown.
[0034] When assembling Li||NCM811 batteries, use 12mm diameter lithium salt-containing NCM811 as the positive electrode, 14mm diameter lithium metal disc as the negative electrode, 17mm diameter polyolefin separator as the substrate, steel sheet as the current collector, spring sheet as the gasket, and assemble 2032 button cells.
[0035] Specifically, the preparation process of lithium salt-containing NCM811 is:
[0036] The positive electrode material NCM811, the conductive agent C45, the binder polyvinylidene fluoride and the lithium salt lithium bis(trifluoromethanesulfonyl imide) were mixed in N-methylpyrrolidone (NMP) solvent in a mass ratio of 7:1:1:1, and magnetically stirred at room temperature for 8 hours to obtain a uniform positive electrode slurry with uniform components and a positive electrode material mass fraction of 16.7%. The slurry was coated on a carbon-coated aluminum foil, and the thickness was controlled to 800 μm by a scraper. The slurry was evenly coated on an automatic coating machine, placed in an oven at 80°C, and vacuum dried for 24 hours. After the solvent evaporated, the lithium salt NCM811 was obtained, and the load was controlled to be 1.9 mg cm -2 .
[0037] First, use a pipette to drop the composite solution C obtained in this embodiment on the positive electrode sheet to fully infiltrate the electrode surface and accelerate ion transmission; then use a pipette to drop the composite solution C obtained in this embodiment on the polyolefin separator to fully infiltrate the substrate to form better contact between the positive and negative electrodes, which is conducive to the deposition of the interface between ions; after the Li||NCM811 battery is packaged, it is placed in a 60°C oven for 12 hours to allow the composite polymer monomer to form a solid high interface strain polymer electrolyte in situ at the interface between the positive and negative electrodes in the battery. After high-temperature curing is completed, the battery is placed in a 30°C constant temperature box and a constant current test is performed at a current density of 1 / 3C at a voltage range of 2.8 to 4.8V. The results are as follows Figure 2 shown.
[0038] When assembling the Li||Li symmetric battery, the only difference from the process of assembling the Li||NCM811 battery is that the lithium metal disc is used as the positive electrode; the other structures and assembly processes remain unchanged. The obtained Li||Li symmetric battery has a current density of 0.1 mA cm -2 The constant current test was carried out at a current density of Figure 3 shown.
[0039] Comparative Example 1
[0040] This comparative example prepares a low interfacial strain polymer electrolyte for a lithium metal battery, which specifically includes the following steps:
[0041] Step 1, adding lithium bis(trifluoromethanesulfonyl)imide into fluoroethylene carbonate, stirring to obtain a precursor solution A with a concentration of 1 M;
[0042] Step 2, mixing hexyl acrylate (as a polymer monomer), azobisisobutyronitrile, polyethylene glycol diacrylate and lithium bistrifluoromethanesulfonyl imide, and stirring to obtain a precursor solution B; wherein the molar ratio between the polymer monomer, the initiator and the cross-linking agent is 100:0.5:1; and the concentration of the lithium salt in the precursor solution B is 2M;
[0043] Step 3, mixing precursor solution A and precursor solution B in a volume ratio of 1:1, and stirring to form a composite solution C;
[0044] Step 4. Using composite solution C as electrolyte, assemble a lithium metal battery, and after drying at 60°C for 12 hours, obtain a low interfacial strain polymer electrolyte formed in situ at the positive and negative electrode interfaces of the lithium metal battery; wherein, according to the ratio of fluorine element to oxygen element in the chemical structure formula of the adopted polymer monomer hexyl n-acrylate, the ratio of fluorine element to oxygen element contained in the low interfacial strain polymer electrolyte segment can be determined, and the ratio is calculated to be 0:2.
[0045] In this comparative example, a transparent battery, a Li||NCM811 battery and a Li||Li symmetrical battery are assembled according to the steps of Example 1 for illustration; wherein, the structural changes of the electrolyte surface of the coated copper foil when lithium ions are released under an optical microscope are as follows: Figure 1 As shown; the results of the constant current test of Li||NCM811 battery at a voltage range of 2.8 to 4.8V and a current density of 1 / 3C rate are as follows Figure 2 As shown; Li||Li symmetric battery at 0.1 mA cm -2 The results of the constant current test at a current density of Figure 3 shown.
[0046] Depend on Figure 1 It can be seen from the deformation diagram of the electrolyte de-Li+ interface over time that the high interface strain polymer electrolyte (denoted as High F / O) obtained in Example 1 has a larger volume change than the low interface strain polymer electrolyte (denoted as Low F / O) obtained in Comparative Example 1 as the transparent battery charging test proceeds. The high interface deformation can effectively reduce the potential difference at the electrolyte / lithium metal interface, which is beneficial to the stable deposition of ions.
[0047] Depend on Figure 2 It can be seen that the Li||NCM811 battery assembled with the high interface strain polymer electrolyte obtained in Example 1 has higher discharge capacity and cycle stability than the Li||NCM811 battery assembled in Comparative Example 1, can effectively stabilize the lithium metal interface ion deposition, inhibit the growth of lithium dendrites, and achieve efficient and uniform utilization of the lithium metal negative electrode.
[0048] Depend on Figure 3 It can be seen that the Li||Li symmetric battery assembled with the high interfacial strain polymer electrolyte obtained in Example 1 can withstand a larger test current density and better cycle stability than the Li||Li symmetric battery assembled in Comparative Example 1.
[0049] In summary, increasing the proportion of fluorine and oxygen in the polymer electrolyte chain segments helps to reduce the coordination strength of Li-O in the polymer electrolyte bulk phase, increase the interfacial volume deformation when the polymer is de-lithium ionized, and thereby reduce the potential difference at the electrolyte / lithium metal interface, homogenize interfacial lithium deposition, inhibit lithium dendrite growth, and ultimately improve the cycle stability of lithium metal batteries.
[0050] Example 2
[0051] This embodiment prepares a high interfacial strain polymer electrolyte for lithium metal batteries. The preparation process is different from that of embodiment 1, except that: the polymer monomer used in step 2 is adjusted to a mixture of 2,2,3,4,4,4-hexafluorobutyl acrylate and butyl acrylate, and the molar ratio of 2,2,3,4,4,4-hexafluorobutyl acrylate, butyl acrylate, initiator and crosslinker is 91:9:0.5:1, thereby obtaining a high interfacial strain polymer electrolyte; wherein, according to the ratio of fluorine element to oxygen element in the chemical structural formula of the polymer monomers 2,2,3,4,4,4-hexafluorobutyl acrylate and butyl acrylate, and the raw material ratio of 2,2,3,4,4,4-hexafluorobutyl acrylate and butyl acrylate, the ratio of fluorine element to oxygen element contained in the high interfacial strain polymer electrolyte segment can be determined, and the calculated ratio of the two is 3:1. The other preparation processes are the same.
[0052] Example 3
[0053] This embodiment prepares a high interfacial strain polymer electrolyte for lithium metal batteries. The preparation process is different from that of embodiment 1 only in that: the polymer monomer used in step 2 is adjusted to a mixture of 1H,1H,2H,2H-nonafluorohexyl acrylate and butyl acrylate, and the molar ratio of 1H,1H,2H,2H-nonafluorohexyl acrylate, butyl acrylate, initiator and crosslinker is 93:7:0.5:1, thereby obtaining a high interfacial strain polymer electrolyte; wherein, according to the ratio of fluorine element to oxygen element in the chemical structural formula of the polymer monomers 1H,1H,2H,2H-nonafluorohexyl acrylate and butyl acrylate, and the raw material ratio of 1H,1H,2H,2H-nonafluorohexyl acrylate and butyl acrylate, the ratio of fluorine element to oxygen element contained in the high interfacial strain polymer electrolyte segment can be determined, and the calculated ratio of the two is 9:2. The other preparation processes are the same.
[0054] Example 4
[0055] In this embodiment, a high interfacial strain polymer electrolyte for lithium metal batteries is prepared. The preparation process is different from that of Example 1, except that the polymer monomer used in step 2 is adjusted to a mixture of 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate and butyl acrylate, and the molar ratio of 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate, butyl acrylate, initiator and crosslinking agent is 95:5:0.5:1, and the obtained High interfacial strain polymer electrolyte; wherein, according to the ratio of fluorine to oxygen in the chemical structure formula of the polymer monomers 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate and butyl acrylate, and the raw material ratio of 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate and butyl acrylate, the ratio of fluorine to oxygen contained in the high interfacial strain polymer electrolyte chain segment can be determined, and the ratio of the two is calculated to be 13:2. The other preparation processes are the same.
[0056] According to the deformation diagram of the electrolyte de-Li+ interface over time of Examples 1 to 4 and Comparative Example 1, the interface shrinkage ratio data of each electrolyte de-Li+ interface was roughly calculated, and the constant current test results of the Li||NCM811 battery assembled with the polymer electrolyte of Examples 1 to 4 and Comparative Example 1 were obtained in the voltage range of 2.8 to 4.8 V and at a current density of 1 / 3C rate, as shown in Table 1. It can be seen that by adjusting the specific components and proportions of the polymer monomers and controlling the ratio of fluorine elements to oxygen elements contained in the obtained high interfacial strain polymer electrolyte segment to be within the range of (5 to 15): (1 to 3), high interfacial volume deformation can be achieved, thereby improving the discharge capacity and cycle stability of the lithium metal battery.
[0057] Table 1
[0058] sample Interface shrinkage ratio 1 / 3C capacity Example 1 33% <![CDATA[180mAh g -1 ]]> Example 2 26% <![CDATA[172mAh g -1 ]]> Example 3 19% <![CDATA[160mAh g -1 ]]> Example 4 9% <![CDATA[152mAh g -1 ]]> Comparative Example 1 1% <![CDATA[120mAh g -1 ]]>
[0059] The present invention uses specific examples to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing a high interfacial strain polymer electrolyte for lithium metal batteries, characterized in that: The following steps are involved: Step 1, adding lithium salt into an organic solvent and stirring to obtain a precursor solution A with a concentration of 0.5 to 3M; Step 2, mixing a polymer monomer, an initiator, a cross-linking agent and a lithium salt, and stirring to obtain a precursor solution B; wherein the molar ratio of the polymer monomer, the initiator and the cross-linking agent is (98-100): (0.5-2): (1-3); the concentration of the lithium salt in the precursor solution B is 0.5-3M; the polymer monomer is at least one of 2,2,3,4,4,4-hexafluorobutyl acrylate, 1H,1H,2H,2H-nonafluorohexyl acrylate, 2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptyl acrylate, and 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate; Step 3, mixing precursor solution A and precursor solution B in a volume ratio of (0.5-2):(1-3), and stirring to form a composite solution C; Step 4: Using the composite solution C as the electrolyte, assembling a lithium metal battery, and after drying, obtaining a high interfacial strain polymer electrolyte formed in situ at the interface between the positive and negative electrodes of the lithium metal battery.
2. The method for preparing a high interfacial strain polymer electrolyte for lithium metal batteries according to claim 1, characterized in that: The polymer monomers also include benzyl acrylate and / or butyl acrylate.
3. The method for preparing a high interfacial strain polymer electrolyte for lithium metal batteries according to claim 2, characterized in that: By adjusting the specific components and proportions of the polymer monomers in the precursor solution B, the ratio of fluorine to oxygen contained in the resulting high interfacial strain polymer electrolyte chain segment is controlled to be (5-15):(1-3), thereby achieving high interfacial volume deformation.
4. The method for preparing a high interfacial strain polymer electrolyte for lithium metal batteries according to claim 3, characterized in that: The organic solvent is at least one of fluoroethylene carbonate, ethylene glycol dimethyl ether, 1,3-dioxolane, diethyl carbonate and dimethyl carbonate.
5. The method for preparing a high interfacial strain polymer electrolyte for lithium metal batteries according to claim 3, characterized in that: The initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate and azobisisobutyramidine hydrochloride.
6. The method for preparing a high interfacial strain polymer electrolyte for lithium metal batteries according to claim 3, characterized in that: The cross-linking agent is polyethylene glycol diacrylate and / or ethylene glycol dimethacrylate.
7. The method for preparing a high interfacial strain polymer electrolyte for lithium metal batteries according to claim 3, characterized in that: The lithium salt is at least one of lithium hexafluorophosphate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium difluorooxalatoborate.
8. The method for preparing a high interfacial strain polymer electrolyte for lithium metal batteries according to claim 3, characterized in that: The drying temperature in step 4 is 60-80° C. and the drying time is 12-24 hours.
Citation Information
Patent Citations
Functional quasi-solid polymer electrolyte as well as preparation method and application thereof
CN115986205A
Preparation method and application of polymer electrolyte
CN117525571A
High-voltage-resistant solid-state battery and preparation method thereof
CN117712499A
In-situ polymerization solid-state electrolyte precursor solution and solid-state battery
CN118063692A
Ion conductive polymer solid electrolyte and battery using this solid electrolyte
JP1999329064A
Cited By
High-ionic-conductivity polymer electrolyte, lithium metal battery and preparation method
CN120933455A
Micro-phase separation high-pressure-resistant high-elasticity solid electrolyte as well as preparation and application thereof
CN121546144A
Micro-phase separation high-pressure-resistant high-elasticity solid-state electrolyte and preparation and application thereof
CN121546144B